The Contribution of Educational Psychology to South African Preservice Teacher Training and Learner Support - Motlalepule Ruth Mampane (MDPI AG, 2023)
Teacher education programmes are developed around the theoretical and practical understanding of child development, learning, assessment, behaviour management and motivation, which are areas of expertise in educational psychology. This paper aims to (a) critically investigate the contribution of educational psychology in the training of preservice teachers at South African universities and (b) understand the distribution of educational psychologists in public schools to support teaching and learning. A narrative literature review and email requests for unpublished documents from four educational psychologists were used as methods to collect literature in order to answer the following questions: What contribution does educational psychology make to training preservice teachers at public universities in South Africa? What contributions do educational psychologists make to support learners in South African public schools? Analysis was carried out by identifying recurring patterns in the literature reviewed. This study found that of the 26 public universities in South Africa, there are only 6 universities that offer educational psychology programmes. Educational psychology programmes in higher education institutions are in decline, leading to a decrease in the number of qualified educational psychologists. This decline negatively affects the involvement of educational psychologists in training preservice teachers in educational psychology modules or courses. Therefore, the inclusion of educational psychology as a core or fundamental module in the curriculum of preservice teachers to avoid dependence on the decreasing number of educational psychologists in higher education institutions is key. An increase in teacher training programmes in higher education should be merged with an equal increase in educational psychology core or fundamental courses in the curriculum of preservice teachers.